Peer-tutoring Worksheet to Improve Student’s Self-efficacies at Department of Educational Sciences, Faculty of Education and Teacher Training, Universitas Lampung - Herpratiwi, Herpratiwi; Firdaus, Rangga; Pradini, Susanthi (FKIP Universitas Lampung, 2023)
Peer-tutoring Worksheet to Improve Student’s Self-efficacies at Departement of Educational Sciences, Faculty of Education and Teacher Training, Universitas Lampung. Objectives: This quantitative approach research investigated the influence of peer tutoring worksheet to improve student’s self-efficacy in learning. Methods: This study involved 56 students at primary teacher education, department of science education, Universitas Lampung. This study used N-Gain analysis and paired sample t-test to find the differences and improvement between pre-test and post-test in self-efficacy after given peer-tutoring worksheet treatment. Finding: Paired sample t-test indicated that there are the significant differences between pre-test and post-test after given peer tutoring worksheet treatment. N-gain analysis also revealed that there is improvement in student’s self-efficacy in learning after using peer-tutoring worksheet method in learning. With peer-tutoring worksheets, students are able to encourage and support each other so it increased student’s self-efficacy. Conclusion: Peer-tutoring worksheet are effective to improve student’s self-efficacy in learning. Keywords: worksheet, peer-tutoring, self-efficacy, studentsDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202323